(untitled) (Journal of Hama University, 2025)
This research aimed to measure the relative efficiency of the University of Hama and the possibility of analyzing it during the period 2015-2020, and to measure the relative efficiency of its colleges using the data envelopment analysis model (DEA) (the output orientation model) in both ways: the fixed returns to scale model and the variable returns to scale model; To find efficiency indicators) as one of the relatively modern methods of nonparametric statistical analysis, and to know whether they enjoyed relative efficiency or not during those years, as well as knowing which colleges achieved complete relative efficiency and which colleges were inefficient, and identifying the colleges that constitute reference units for the rest of the colleges that did not achieve relative efficiency. Complete. The number of students and the number of faculty members were used as inputs to the model, while the number of graduates was used as an output of the model. Many conclusions were reached, the most important of which are: The University of Hama was relatively efficient in 2018, and this can be used as guidance. The College of Education was efficient and can be considered an appropriate reference unit for the rest of the colleges at the University of Hama